EFFECT OF MINDFULLNESS THERAPY ON THE LEVEL OF ANXIETY OF POSTPARTUM MOTHERS IN MALINGPING INPATIENT HEALTH CENTER YEAR 2022 - Adiba Perwirasari; Ita Herawati (International Journal Of Health Science, 2023)
Background : Postpartum anxiety is very important to know because of the mother's lack of knowledge at this stage, because it will undergo many changes both emotional (psychologically), physical (physiological) changes and environmental (social) changes experienced by postpartum mothers. Such changes can affect the emotional instability of the mother after childbirth, which is characterized by a deep and sustained feeling of fear or worry. Continued postpartum anxiety negatively affects both mother and baby. The anxiety rate of postpartum mothers is still a high category in various countries such as Pakistan as much as (70%), Hong Kong as much as (54%), Bangladesh as much as (29%) and Portugal as much as (18.2%) %), anxiety levels in Indonesia as much as (28.7 %) (Agustin and Septiyana, 2018). Mindfulness therapy can be used to reduce the level of anxiety towards postpartum mothers, when a person is in a mindfulness situation, the emotional stability of postpartum mothers will be more improved, and the effect is regarding the decrease in anxiety levels (Triyono. H. G, Dwidiyanti, M. & Widyastuti, 2018). According to Oktavia (2018), defining mindfulness therapy aims to help a person in gaining awareness so that there is no reaction to what is happening (good, bad or neutral events / events) and a person is able to overcome his emotions when in a state of depression or frustration and build peace for himself.